Synthesis and Characterization of New Mannich Bases Derived from 7-hydroxy-4-methyl Coumarin - Baghdad Science Journal (Baghdad Science Journal, 2016)
Coumarin is a natural substance isolated from different plants. It belonges to a group of benzobyrones which consists of a benzene ring joined to a pyrone nucleus. In the present research, a new series of coumarin derivatives were formed. Compound (1) (7-hydroxy-4-methyl Coumarin) was converted into 4-methylquinolin-2(H) derivative (2) by reaction with acetamide, and then reaction of (2) with thiosemicarbazide in ethanol leads to the synthesize of hydrazincarbothioamide derivative (3).The reaction of (3) with ethylchloroacetate in presence of sodium acetate leads to closure ring to get [(1-(5-oxo-2-thioxoimidazolidin-1-ylimino) ethyl)]quinolin-2(1H)-one (4). Mannich bases were prepared through the reaction of (4) with primary amines to form compounds (5-6). New coumarin derivatives were characterized by their physical properties and various spectral analysis like: FTIR, 1HNMR spectra and GC-Mass spectrum for some of them.